Ziziphora clinopodioides Essential Oil and Nisin as Potential Antimicrobial Agents against Escherichia coli O157:H7 in Doogh (Iranian Yoghurt Drink). (13th December 2015) - Shahbazi, Yasser
Abstract : The aim of the present study was to evaluate the effects of Ziziphora clinopodioides essential oil (0.1 and 0.2%) and nisin (250 and 500 IU/mL) separately and in combination on survival of Escherichia coli O157:H7 inoculated in Doogh (Iranian yoghurt drink) during storage under refrigerated temperature (4 ± 1°C) for 9 days. Viability of Lactobacillus casei at different concentrations of Z. clinopodioides essential oil (0.1 and 0.2%) in Doogh was also examined. The major components were carvacrol (64.22%), thymol (19.22%), γ -terpinene (4.63%), andp -cymene (4.86%). There was no significant difference (p > 0.05 ) between samples treated with nisin and those of untreated samples. Samples treated with both concentrations of the essential oil (0.1 and 0.2%) showed populations of E. coli O157:H7 significantly (p < 0.05 ) lower than those of untreated samples. The essential oil of Z. clinopodioides in combination with nisin had a potential synergistic effect against E. coli O157:H7 in Doogh samples after 5 days. The count of L. casei was not inhibited by different concentrations of the Z. clinopodioides essential oil. It is concluded that the leaf essential oil of Z. clinopodioides in combination with nisin can be applied as alternative antimicrobial agents in Doogh to inhibit the growth of E. coli O157:H7.